Sulfhydryl-dependent attachment of Treponema denticola to laminin and other proteins. - Haapasalo, M (1991)
Attachment of Treponema denticola ATCC 35405 to laminin, a major basement membrane protein, and to other proteins was studied. Microdilution plates were coated with the proteins, and the attachment of T. denticola was measured by the enzyme-linked immunosorbent assay technique. Compared with bovine serum albumin (BSA), T. denticola had a high affinity to laminin, fibronectin, fibrinogen, and gelatin, as well as to type I and type IV collagens. Attachment to RGD peptide (Gly-Arg-Gly-Asp-Ser, the integrin recognition sequence) was only about 30% of that to laminin and was comparable to attachment to BSA. Tests with laminin fragments obtained through elastase digestion showed that the spirochetes attached well to an A-chain 140-kDa fragment involved in eukaryote cell attachment but did not attach to a 50-kDa fragment that includes the heparin binding site. Pretreatment of T. denticola with soluble laminin, fibronectin, gelatin, BSA, or fibrinogen had no effect on the attachment of the bacteria to laminin or fibronectin. A wide variety of compounds were tested for their possible inhibitory actions on the attachment. While most treatments of T. denticola ATCC 35405 had little or no effect on the attachment to proteins, sulfhydryl reagents p-chloromercuribenzoic acid (pCMBA) and oxidized glutathione inhibited the attachment by 70 to 99%, depending on the protein. When T. denticola was first allowed to attach to proteins, addition of pCMBA or oxidized glutathione could no longer reverse the attachment. Heat treatment of the spirochetes also markedly reduced the attachment to laminin, gelatin, and fibrinogen but not to BSA. Mixed glycosidase treatment of the spirochetes inhibited the attachment by 20 to 80%. None of the above treatments of the substrate proteins had any marked effect on the spirochete attachment. The results indicate that T. denticola has the capacity to bind to many different kinds of proteins by utilizing specific attachment mechanisms. The binding appears to involve protein SH groups and/or carbohydrate residues on the surface of T. denticola.